One stage atrioventricular nodal ablation and leadless pacemaker implantation for refractory atrial fibrillation - Chu‐Pak Lau; Kathy Lai‐Fun Lee (Journal of Arrhythmia, 2019)
Abstract Atrioventricular nodal (AVN) ablation and right ventricular (RV) pacing is recommended for refractory atrial fibrillation (AF) and tachycardia‐bradycardia syndrome. Three AF patients (mean age 83, range 79‐89 years) underwent AVN ablation and transvenous leadless pacemaker Micra™ implantations using the same venous access without anticoagulation interruption. Satisfactory pacing 0.59 (0.50‐0.63) V at 0.24 ms and sensing 11.2 (6.3‐15.6) mV were achieved within 1‐3 deployments. There were no vascular complications nor device dislodgment. Durable pacemaker parameters and VVIR pacing were achieved. Combined AVN ablation and leadless pacemaker implantation is feasible and safe, and avoids pacemaker pocket hematoma and bleeding complications in patients on uninterrupted anticoagulation.